KLASIFIKASI DATA PELANGGAN POTENSIAL PUT IN SERVICE INDIHOME MENGGUNAKAN ALGORITMA NAÏVE BAYES - Dwi Wibowo, Muhammad Fauzan Al-Ghifary; Rahmadewi, Reni (Power Elektronik : Jurnal Orang Elektro, 2024)
In the digital era like now, the invitation to get a job is very tight, companies are also increasingly demanding prospective employees to have work experience. This experience allows them to know and understand the atmosphere and apply the knowledge gained during college to the world of work. Knowing and learning how to classify customer data, an opportunity for students to gain experience. Data is an observation result in the form of characteristics of the representation that represents an object. While the understanding of information is the result of structured input processing [1]. Classification is an information mining functionality that wants to create a model to predict part of the objects in the information line [2]. Naïve Bayes algorithm is a grouping of data that is needed when predicting the possibility of a class. The customer classification of test data and training data required for grouping is 25 test data and 75 training data, where training information is then processed using the nave Bayes procedure [6]. After the grouping process using the nave Bayes procedure ended, after that the test information experiment amounted to 25 customer information [7]. Suggestions for further research, the method used needs to be redeveloped using other data mining methods, and it is better if the data used needs to be integrated with the database in order to avoid duplication or damage to data and data security is better maintained.